Effect of tidal volume on gastric insufflation during laparoscopic cholecystectomy: a strictly retrospective observational study - Zhao, Xiaolong; Zhao, Jinyang; Zhang, Chengjiang (Frontiers in Surgery, 2026)
BackgroundLaparoscopic cholecystectomy (LC) is the gold-standard minimally invasive gallbladder removal procedure. Optimal ventilation during LC requires positive end-expiratory pressure (PEEP) and low tidal volumes (TV) to prevent gastric insufflation (GI), which may cause regurgitation and cardiopulmonary complications.MethodThis strictly retrospective observational study analyzed routine collected data from 60 patients undergoing laparoscopic cholecystectomy between January 2022 and December 2023. Patients were categorized into three groups based on anesthesia records of delivered tidal volumes (6, 8, or 10 mL/kg) during facemask ventilation. While group assignment was performed retrospectively, ventilation parameters were standardized per institutional protocol, ensuring consistent clinical delivery. Patients were divided into Group 1 (6 mL/kg), Group 2 (8 mL/kg), and Group 3 (10 mL/kg). Gastric insufflation was assessed via ultrasonography, and respiratory parameters end-tidal carbon dioxide (PetCO2), end-tidal oxygen (ETO2), and peak inspiratory pressure (PIP) were recorded.ResultGI incidence was significantly higher in Group 3 (60%) vs. Group 1 (15%, p = 0.0079) and Group 2 (20%, p = 0.0225). Group 3 showed greater antral area expansion post-ventilation (504.1 ± 109.8 mm2 vs. 420.1 ± 47.1 mm2, p = 0.001). PetCO2 and ETO2 levels differed significantly across groups (p < 0.001).ConclusionThe study reveals that Group 2’s facemask ventilation may improve preoxygenation and minimize gastric insufflation during laparoscopic cholecystectomy anesthesia induction. Further research is needed due to the small sample size, ultrasonography accuracy issues, and a single-center scenario.